Observasi Perilaku Cacing Tanah Metaphire sp. Sebagai Upaya Awal Domestikasi: Behavioural Observation of Earthworm Metaphire sp. as an Initial Domestication Effort - Dewi Karmila; Tri Heru Widarto (Departemen Biologi, Institut Pertanian Bogor, 2023)
Earthworms play many roles, comprising processing soil, improving soil fertility, and being an ingredient in various products (e.g., medicine and cosmetics). Therefore, earthworms are widely cultivated. The Indonesian worm, Metaphire sp., constitutes a large biomass but has not been widely researched and cultivated. Domestication is a necessary first step in facilitating cultivation and husbandry. This study aims to determine the natural daily behavioral pattern of adult Metaphire sp. earthworms at the individual level. This research was conducted by collecting and keeping a stock of worms. Then, we observed the natural behavior of Metaphire sp. on and under the soil surface (through a glass terrarium) for seven days each. Observed parameters for each behavior were recorded in the ethogram table. We also sketched and recorded the length of the excavated tunnel. During the day, Metaphire sp. showed predominantly resting or inactive behavior, mostly occurring under the soil surface. Metaphire sp. comes to the ground mostly in the evening. Based on these results, the peak activity of Metaphire sp. can be stated that it takes place at night from 18.00-23.00. At night, Metaphire sp. appeared and did most activities on the surface. We conclude that Metaphire sp. is most active at night, from 18.00- 23.00.